2007
DOI: 10.1203/pdr.0b013e3180457623
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Origins of β-Cell Failure in Type 2 Diabetes: The Role of Epigenetic Mechanisms

Abstract: Intrauterine growth retardation (IUGR) has been linked to later development of type 2 diabetes in adulthood. An abnormal metabolic intrauterine milieu affects the development of the fetus by permanently modifying gene expression of susceptible cells. Altered gene expression persists after birth, suggesting that an epigenetic mechanism may be responsible for changes in transcription. Uteroplacental insufficiency (IUGR) is associated with hypomethylation and hyperacetylation of genomic DNA in brain and liver of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 45 publications
0
37
1
2
Order By: Relevance
“…In this study, we did not find a significant correlation between DNMT1 expression and proliferative activity, as indicated by the proliferative labeling results of Ki67 and PCNA. Recently, several studies identified a role for environmental factors in regulating epigenetic modifications (39)(40)(41)(42). Our analysis of the correlation between patient life styles, such as smoking and alcohol consumption, and the expression of DNMT1 and HDAC1, showed no significance.…”
Section: ------------------------------------------------------------contrasting
confidence: 56%
“…In this study, we did not find a significant correlation between DNMT1 expression and proliferative activity, as indicated by the proliferative labeling results of Ki67 and PCNA. Recently, several studies identified a role for environmental factors in regulating epigenetic modifications (39)(40)(41)(42). Our analysis of the correlation between patient life styles, such as smoking and alcohol consumption, and the expression of DNMT1 and HDAC1, showed no significance.…”
Section: ------------------------------------------------------------contrasting
confidence: 56%
“…alteration in DNA methylation. It is also widely accepted that chemicals as well as altered dietary intake would affect DNA methylation during gestation [Simmons, 2007] especially during gametogenesis [Anway et al, 2005] at a point when methylation machineries are highly active and cells are undergoing rapid cell division. It is difficult to accept however that environmental agents could affect DNA methylation patterns throughout life well after tissues and organs are formed and their methylation pattern is established.…”
Section: How Could Behavior Modulate Dna Methylation? the Dynamic Patmentioning
confidence: 99%
“…In the pathogenesis of T2D, special attention has been given to the role of intrauterine DNA methylation and imprinting for the programming of diabetogenic effects later in life (103 ). An interesting study by Dabelea et al has shown that intrauterine exposure to diabetes increases the risk of diabetes and obesity in the offspring compared to siblings who were born before their mothers' onset of diabetes (104 ).…”
Section: Epigeneticsmentioning
confidence: 99%